A legal odyssey: denazification law, Nazi elite schools, and the construction of postwar memory. Issue 4 (4th July 2017) - Mueller, Tim
Abstract: This article examines the responses of former Nazi elite school staff to the pressures of denazification. Teachers of the National Political Education Institutes, known as Napolas for short – boarding schools for the Third Reich's racial elite – were especially affected by the purge of National Socialist supporters from positions of influence, due to the schools' intimate relationship to Heinrich Himmler's SS. The introduction of the Law for Liberation from National Socialism and Militarism in the US occupation zone in 1946, however, allowed Napola apologists to construct a selective interpretation of the past, which rehabilitated the Napolas' postwar image and successfully reintegrated alumni into West German society, in many cases long before the Adenauer government issued a series of amnesty laws.